2018
DOI: 10.1093/aob/mcy130
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the flower – developmental aspects of sex chromosome evolution

Abstract: We integrate the genic, genomic and epigenetic levels of sex determination and stress the impact of sex chromosome evolution on structural and functional aspects of plant sexual development. We also discuss the impact of dioecy and sex chromosomes on genome structure and expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 204 publications
0
10
0
Order By: Relevance
“…This sex leakiness was mapped to the Y chromosome [22]. This result has recently been confirmed using zebularine, another DNAhypomethylating drug [23]. This epigenetic state can then be passed to the next generation from father to sons only.…”
Section: (A) the Epigenetics Of Sex Labilitymentioning
confidence: 77%
“…This sex leakiness was mapped to the Y chromosome [22]. This result has recently been confirmed using zebularine, another DNAhypomethylating drug [23]. This epigenetic state can then be passed to the next generation from father to sons only.…”
Section: (A) the Epigenetics Of Sex Labilitymentioning
confidence: 77%
“…Sex chromosomes evolved from autosomes [ 35 ]. The existence of SDR is the distinguishing features of nascent sex chromosomes in land plants [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hobza (IBP) showed that separated sexes evolved independently and repeatedly in about 5 % of plant species. In many species, dioecy has evolved recently, so these plants provide an excellent model for studying the early stages of sex chromosome divergence, which later in evolution leads to gradual sex chromosome degeneration (Hobza et al 2018). Z. Kubát (IBP) showed that some TEs proliferate preferentially either in the male or in the female germline which can be connected with specific circumstances affecting TE management and activity in male and female plants and during gametophyte formation (Jesionek et al 2021).…”
Section: Unravelling the Mysteries Of Plant Sex-and B-chromosomesmentioning
confidence: 99%